2012
DOI: 10.1097/ta.0b013e31825ff670
|View full text |Cite
|
Sign up to set email alerts
|

“SCIP”ping antibiotic prophylaxis guidelines in trauma

Abstract: Our results suggest that SCIP antibiotic prophylaxis guidelines effectively reduce the risk of SSI in patients undergoing trauma laparotomy. Despite the emergent nature of operative procedures for trauma, efforts to adhere to these antibiotic guidelines should be maintained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…In our study, 23.5% of patients developed extra abdominal complications. These complications were: 6.3% pneumonia, 3.1% deep vein thrombosis, 4.5% melena, 5% acute renal insufficiency, and 4.5% multiple organ dysfunction syndrome.…”
Section: Morbidity and Mortalitymentioning
confidence: 91%
See 1 more Smart Citation
“…In our study, 23.5% of patients developed extra abdominal complications. These complications were: 6.3% pneumonia, 3.1% deep vein thrombosis, 4.5% melena, 5% acute renal insufficiency, and 4.5% multiple organ dysfunction syndrome.…”
Section: Morbidity and Mortalitymentioning
confidence: 91%
“…Smith BP et al (23) concluded that antibiotic prophylaxis guidelines clearly reduce the risk of SSI in patients undergoing trauma laparotomy. Sharp JP et al (24) observed that operative decisions for dealing with colon injuries based on a defined algorithm improve outcomes.…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%
“…Generally, antibiotic prophylaxis recommendations are related to specific injury patterns and surgical procedures that transpire in civilian life. 1-7 However, in response to the unique injury patterns and care situations associated with military deployment, along with a rise in the rate of infectious complications among wounded service members, 8-13 a CPG for combat-related infection management was published in 2008 by an expert consensus group convened by the Department of Defense (DoD) Joint Trauma System (JTS) and comprised of military and civilian authorities. 14 …”
Section: Introductionmentioning
confidence: 99%
“…Even though SCIP measures have not yet been recommended for use in trauma cases, these data demonstrated that the antibiotic prophylaxis guidelines effectively reduced the risk of SSI in this patient population. 17 The weighted aggregate odds ratio for these 5 papers was .82 or a calculated 18% decrease in odds of developing SSI. While short of the 25% goal, this represents a substantial reduction in SSI with comprehensive compliance with SCIP measures.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, continued administration of preventative antibiotics beyond 24 hours postoperatively was demonstrated to not improve outcomes. 9,13,16,17 In 1970, the Centers for Disease Control and Prevention (CDC) established the National Nosocomial Infections Surveillance (NNIS) system to monitor the rates and trends in nosocomial infections. 11 NNIS has since transitioned into the National Healthcare Safety Network.…”
mentioning
confidence: 99%